Risk factors and the prevention of oral clefts - Vera Lúcia Gil-; Isabella Lopes Monlleó (Sociedade Brasileira de Pesquisa Odontológica, 2014)
This article presents general aspects of risk factors and particularities of the management of individuals with oral clefts (OCs). A practical manual of prevention and management of this congenital defect was prepared based on a review of the literature and using data from Brazilian multicenter studies. Since OCs require efforts from all levels of healthcare, the data herein presented permits appropriate follow-up for affected individuals and their families. Also, the recognition of risk factors is crucial for planning and implementing preventive measures at the individual and population levels.